Advertising Effectiveness and Attitude Change Vary as a Function of Working Memory Capacity. Issue 6 (November 2016) - Sanchez, Christopher A.; Alley, Zoe M.
Summary: Prior research has confirmed that the amount of attention paid to an advertisement will influence its effectiveness when it comes to changing consumer attitudes. This study expands on this understanding by exploring how individual differences in the ability to control attention (i.e., working memory capacity; WMC) might further moderate the effect of attention on advertising. Participants who varied in WMC were evaluated on their attitudes towards a consumer brand before and after viewing a video advertisement. While the advertisement did make participants more positive towards the product overall, this change in attitude was directly related to participants' ability to control attention and the degree to which the ad fostered the activation of autobiographical memories. Further, these changes in attitude were unrelated to how well the ad was remembered. This suggests that individual differences in attentional control can influence how advertisements impact customer attitude and the acceptance of persuasive messaging. Copyright © 2016 John Wiley & Sons, Ltd.